Large hole polarons in Sc-doped TiO2 crystals - Stashans, A. (2013)
First-principles calculations based on the density functional theory (DFT) within the generalized gradient approximation (GGA) have been used to study Sc-doped TiO2, rutile and anatase, crystals. Local defect microstructure, electronic and electrical properties have been obtained and discussed in the present work. Large radius hole polaron state found here points out to the possibility of p-type electrical conductivity in Sc-doped titania.